Inclusive orchestral music therapy according to the Euterpe Method: a multimodal framework for neurodevelopmental disorders - Liuzzi, Tommaso; D’Arienzo, Fiammetta; Staccioli, Susanna; Slaïby, Rita Faraj; Harb, Maroun Bou Sleiman; Tarabay, Miled; Giuliani, Roberto; Chirico, Teresa; Lettori, Donatella; Castelli, Enrico (Frontiers in Neurology, 2025)
Neurodevelopmental disorders (NDD), as defined by DSM-5-TR and CDDR, comprise heterogeneous early-onset conditions involving executive dysfunction, motor planning deficits, language impairments, and socio-emotional dysregulation. Evidence from neuroimaging and clinical studies suggests that music-based interventions may engage distributed neural networks—including fronto-striatal, temporo-parietal, limbic, and brainstem circuits—through predictive timing, cross-modal synchronization, and adaptive plasticity. However, clinical translation has been hindered by methodological heterogeneity, insufficient standardization, and reduced reproducibility, together with limited integration of clinical, functional, and neurophysiological indicators, absence of unified protocols combining individualized and orchestral modules with explicit transfer mechanisms, and insufficient monitoring of fidelity and multisite feasibility. This perspective proposes the IncluSive Orchestral mUsic therapy accordiNg to the euterpe methoD (I-SOUND), a clinically adapted orchestral framework structured to integrate three complementary modules: Individual Music Therapy (IMT), an Orchestral Music Therapy module (OMT), and a Multidirectional and Iterative Transfer Process (MIT-P). Developed from the progressive refinement of the Euterpe Method and the pediatric EM Active algorithm, the model is intended to target specific neurofunctional domains and to explore generalization to everyday contexts. A two-phase evaluation—comprising an observational study followed by a randomized controlled trial—is planned to assess feasibility, fidelity, sustainability, and clinical applicability in heterogeneous NDD populations. Particular attention is given to the methodological challenge of balancing ethical inclusion with internal validity. No efficacy claims are advanced, as the framework requires empirical verification before clinical conclusions can be drawn.